Structure, development and growth of selection forests at the Granata research site - Reščič, Matej (Zbornik gozdarstva in lesarstva, 2007)
The Granata research site was established for the study of structure, growth and regeneration of silver fir-European beech single stem selection forest. Three phytocoenological relevés were carried out, all trees ?5 cm diameter at breast height (d.b.h.) were measured by full callipering, tree growth was analysed for sample trees, regeneration of tree species was registered on 63 sampling plots. In addition, historical data from past forest inventories werestudied. In the period from 1952 to 2003, the share of silver fir has decreased from 86% to 26%, the share of Norway spruce increased significantly,whereas the share of beech and sycamore has slightly increased. The current growing stock amounts to 350 m3 ha-1, with large-size diameter trees (d.b.h. ?50 cm) representing 51% of total growing stock. The site is divided into 16 stand patches with significant differences in tree species composition and diameter distribution. Regeneration is sufficient with silver fir prevailing in total number of seedlings (42%). 23% of all seedlings are damaged as a result of game browsing.
Keywords: fitocenologija; lesna zaloga; phytosociology; prebiralni gozd; sestoji